Penerapan Metode Certainty Factor Dan Forward Chaining Pada Sistem Pakar Berbasis Web Dalam Mendiagnosis Penyakit Lambung - Nugraha, Ayu Oktavia; Voutama, Apriade; Purwantoro, Purwantoro (Peneliti.net, 2024)
The increasing need for technology that is soaring at this time, makes us required to follow every development, even in the field of health sciences. Where people now really need a health system that can provide information and can also diagnose diseases, especially gastric disease which is still often considered a harmless disease, in fact this disease can cause other dangerous diseases that can result in death if not treated immediately. Therefore, a website-based expert system was built to diagnose gastric disease. This system uses certainty factor and forward chaining methods, and uses the PHP programming language and MySQL database. The object of this study only focuses on gastric disease, namely GERD, Gastritis, and Stomach Cancer. The certainty factor method is a mathematical theory based on the belief and uncertainty function of an expert. Testing the accuracy of the system from the results of the diagnosis gets a percentage of 95%.